Pathways to ischemic neuronal cell death: are sex differences relevant? - McCullough Louise D; Lang Jesse T (Journal of Translational Medicine, 2008)
Abstract We have known for some time that the epidemiology of human stroke is sexually dimorphic until late in life, well beyond the years of reproductive senescence and menopause. Now, a new concept is emerging: the mechanisms and outcome of cerebral ischemic injury are influenced strongly by biological sex as well as the availability of sex steroids to the brain. The principal mammalian estrogen (17 β estradiol or E2) is neuroprotective in many types of brain injury and has been the major focus of investigation over the past several decades. However, it is becoming increasingly clear that although hormones are a major contributor to sex-specific outcomes, they do not fully account for sex-specific responses to cerebral ischemia. The purpose of this review is to highlight recent studies in cell culture and animal models that suggest that genetic sex determines experimental stroke outcome and that divergent cell death pathways are activated after an ischemic insult. These sex differences need to be identified if we are to develop efficacious neuroprotective agents for use in stroke patients.